Strategy for Sustainable Village Status Improvement in Kundur Village Kepulauan Meranti District - Dadang Mashur; Yuni Novita Putri (Indonesian Association for Public Administration (IAPA), 2020)
This research discusses about strategies to sustainable improve village status in the village of Kundur, Kepulauan Meranti Regency. The problems and phenomena in this study are the selection of Kundur village to be one of the priority development target villages, the lower the IKE value in 2018-2019, and the IDM calculation 2018-2019 The purpose of this research (1) to find out the social, economic and ecology conditions in the Kundur village, (2) to find out the strategies carried out to continuously improve the status of the Kundur village. The research method used is a mixed method. From the results of the study, the existing conditions of social security get a sccore of 0,878 economic resilience of 0,600 ecology resilience of 0,850. From the results of these scores get the Kundur village IDM score of 0,776. And the strategy that should be carried out by the Kundur village to improve the status of thee village is anaggresive and growing strategy, by making utilizing human resources in maintaining natural resources for sustainable development, innovation in adding village owned business entity (BUMDes) units in accordance with existing conditions, and addition of plantation production types.